2015
DOI: 10.1007/s10616-014-9819-8
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of basal media and serum for in vitro expansion of suspension peripheral blood mononucleated stem cell

Abstract: Transplantation of stem cells requires a huge amount of cells, deeming the expansion of the cells in vitro necessary. The aim of this study is to define the optimal combination of basal medium and serum for the expansion of suspension peripheral blood mononucleated stem cells (PBMNSCs) without resulting in loss in the differentiation potential. Mononucleated cells were isolated from both mice and human peripheral blood samples through gradient centrifugation and expanded in α-MEM, RPMI, MEM or DMEM supplemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Previous study demonstrated that alkaline phosphatase (ALP) activity and ability to form mineralized deposits were higher in MEM cultures than in DMEM cultures ( 31 ). Zainal et al and Salehinejad et al also revealed that α-MEM supported the expansion and differentiation of MSCs more strongly than DMEM ( 32 , 33 ). So, we decided to use MEM instead of DMEM in the optimized osteogenic and adipogenic medium.…”
Section: Discussionmentioning
confidence: 96%
“…Previous study demonstrated that alkaline phosphatase (ALP) activity and ability to form mineralized deposits were higher in MEM cultures than in DMEM cultures ( 31 ). Zainal et al and Salehinejad et al also revealed that α-MEM supported the expansion and differentiation of MSCs more strongly than DMEM ( 32 , 33 ). So, we decided to use MEM instead of DMEM in the optimized osteogenic and adipogenic medium.…”
Section: Discussionmentioning
confidence: 96%
“…Presently, adult stem cells are the focus of most stem cell research because adult stem cells offer hope for stem cell therapy to treat disease in the future and ethical issues do not preclude its use. Adult stem cells can be obtained from a variety of sources such as peripheral blood (PB) ( Zainol Abidin et al., 2010 ; Yusof et al, 2011 ; Muniandy et al., 2013 ; Zainal Ariffin et al., 2016 ), dental pulp tissue ( Nur Akmal et al., 2014 ; Kermani et al, 2014 ; Hagar et al, 2021 ; Intan Zarina et al., 2022 ), bone marrow (BM), and periodontal ligament tissue ( Chong et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the composition of basal medias has a significant impact on the results of their experiments (Ariffin et al, 2016;Kim et al, 2015;Pirsko et al, 2018;Selenius et al, 2019;Tomoya Kawakami, 2016). However, culture media and supplementation remain a largely overlooked experimental parameter.…”
Section: Introductionmentioning
confidence: 99%